Effects of Spirulina Supplementation on C‐Reactive Protein (CRP): A Systematic Review and Dose–Response Meta‐Analysis - Shahraki Jazinaki, Mostafa; Rashidmayvan, Mohammad; Rahbarinejad, Pegah; Shadmand Foumani Moghadam, Mohammad Reza; Pahlavani, Naseh (Food science & nutrition, 2025)
ABSTRACT The preceding research has produced varied results concerning the impact of Spirulina supplementation on C‐reactive protein (CRP) levels, considered one of the primary risk factors associated with inflammation in chronic conditions. We aimed to understand the potential relationship between Spirulina supplementation and human CRP modulation by performing a meta‐analysis. A comprehensive search was conducted up to February 2024 on prominent medical bibliographic databases, including Web of Science, Scopus, and PubMed, to identify relevant studies. The overall effect size was calculated using a random‐effects model that was proposed by DerSimonian and Laird. The pooled effect size was expressed as weighted mean differences (WMD) with 95% confidence intervals (CI). Furthermore, the heterogeneity between the included studies was evaluated using Cochran's Q test and the I2 statistic. Our meta‐analysis included 7 trials with 283 subjects and 10 effect sizes. Spirulina supplementation significantly reduced serum CRP levels compared to the control group (WMD: −0.55 mg/L; 95% CI: −0.90 to −0.21; p = 0.002). However, heterogeneity among the studies was high (I2 = 86.7%, p < 0.001). Furthermore, no significant linear and non‐linear relationship between supplementation features (dosage and duration) and changes in CRP levels was detected. The results of the current systematic review and meta‐analysis suggest that the intake of Spirulina can cause significant decreases in CRP levels. However, more extensive and well‐executed studies are still needed to draw definitive conclusions regarding this effectiveness. Our meta‐analysis, which combined data from seven trials (with 10 arms), revealed that Spirulina supplementation led to a significant decrease in C‐reactive protein levels compared to control groups.